Explaining Commitment in Romantic Relationships among Emerging Adults: The Role of Disorganised Attachment and Quality of Alternatives - Ainurrohmah, Dinda; Pratiwi, Pradipta Christy (Universitas Ahmad Dahlan, 2025)
Rising relationship ambiguity challenges commitment stability during emerging adulthood. This cross-sectional correlational study examines the predictive role of disorganised attachment and quality of alternatives on romantic commitment. The participants included 215 emerging adults (aged 18–29) in heterosexual dating relationships, selected using purposive sampling. Data were collected using the Adult Disorganised Attachment scale and the Investment Model scale. All procedures were conducted in accordance with ethical standards. Data were analysed using multiple linear regression with robust standard errors. The results indicated that both predictors simultaneously predicted commitment (R2 = 0.38). Partial analysis revealed that the quality of alternatives (β = -0.52) had a dominant negative prediction on commitment compared to disorganised attachment (β = -0.20). Findings suggest that perceived attractive alternatives significantly undermine commitment stability. This highlights the need for counselling interventions addressing attention to alternatives to enhance relationship stability.